PENGARUH SUBSTITUSI TEPUNG TALAS TERHADAP KUALITAS CUPCAKE - Sari, Nita Arlan; Syarif, Wirnelis; Holinesti, Rahmi (Journal of Home Economics and Tourism, 2015)
This research wasaimed toanalyze the effectsubstitution oftaro flouras much15%, 30% and45% of thewheat flourusedforexternalquality(volume, colorandsymmetricalround shape) andinternalquality(texture soft, fragrantscentandsweet taste) oncupcake.The research was atrueexperimentwithcompletely randomized designmethodusing threerepetitionswith30panelists. The results showedthat thesubstitutioneffect on the qualityof taroflourvolume, symmetricalroundshape, texturesoft, fragrantscentandsweet flavorthat wasgenerallythe best valuethere wasin treatment15% (X1) and theeffect on the qualityof colorthatthere wasthe best valuein thetreatment of45% (X3). Keywords: Taro flour substitution, cupcake quality